PENGARUH KEMISKINAN DAN PERTUMBUHAN EKONOMI TERHADAP INDEKS PEMBANGUNAN MANUSIA DI PROVINSI RIAU - Novita Dewi; Yusbar Yusuf; Rita Yani Iyan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to determine the effect of economic growth on poverty and human development index in Riau Province. The data used is secondary data with cross section including data one year in every district in the province of Riau on each variable used.This secondary data sourced from the Central Statistics Agency Pekanbaru. Methods of data analysis used in this research is quantitative method with data analysis and linear regression analysis using SPSS. In this model the independent variable used is the Poverty and Economic Growth. While the dependent variable is the Human Development Index. The result showed that first, Poverty and significant effect on the human development index in the province of Riau. From equation known poverty variables showed a coefficient of -0.079 means that if there is an increase poverty by 1% will decrease the HDI of 0.079% means that every increase in poverty would decrease the percentage of HDI in Riau Province. For poverty variables obtained t is greater than t table so Ho rejected Ha accepted. Second, Economic growth showed a coefficient of 0.024 means that if there is a change of economic growth of 1% there will be changes to the HDI of 0.024% means that any changes in the economic growth will affect the percentage of HDI in Riau Province.Keyword : Poverty, Economic Growth, and Human Development Index.